A Low Cost Desktop Electrochemical Metal 3D Printer. Issue 10 (28th August 2017) - Chen, Xiaolong; Liu, Xinhua; Childs, Peter; Brandon, Nigel; Wu, Billy
Abstract: Additive manufacturing (AM), or 3D printing as it is more commonly known, is the process of creating 3D objects from digital models through the sequential deposition of material in layers. Electrochemical 3D printing is a relatively new form of AM that creates metallic structures through electrochemical reduction of metal ions from solutions onto conductive substrates. The advantage of this process is that a wide range of materials and alloys can be deposited under ambient conditions without thermal damage and more importantly at low cost, as this does not require expensive laser optics or inert gas environments. Other advantages include the fact that this process can be both additive and subtractive through reversal of potential allowing for recycling of components through electrochemical dissolution. However, one main limitation of this technology is speed. Here, a novel electrochemical 3D printer design is proposed using a meniscus confinement approach which demonstrates deposition rates three orders of magnitude higher than equivalent systems due to improved mass transport characteristics afforded through a mechanical electrolyte entrainment mechanism. Printed copper structures exhibit a polycrystalline nature, with decreasing the grain size as the potential is increased resulting in a higher Vickers hardness and electronic resistivity. Abstract : A low‐cost electrochemical metal 3D printer using a meniscus confinement approach is described. The novel design prints polycrystalline copper structures at a volumetric deposition rate three orders of magnitude higher than equivalent systems. The measurements indicate that samples have increased hardness and resistivity compared to cold worked copper. This approach opens the possibility for low cost and multi‐material metal additive manufacturing.